Mindfulness and Psychological Wellbeing iOS App Leveraging the OpenAI API - Ronec, Simon; Valový, Marcel; Buchalcevová, Alena, 1958-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis explores the development and impact of an iOS mobile application leveraging OpenAI models, their API and underlying technologies to improve and enhance its users’ mental health and psychological well-being. The main theoretical frameworks for this study are the Self-Determination Theory and Cognitive-Behavioural Therapy. The developed application offers personalised mental health and well-being support through AI-driven interactions, conversations through the AI chatbot, and structured exercises for well-being and mindfulness improvement. The research used a mixed-methods methodology to evaluate the effects of the developed application, including both quantitative assessments and qualitative interviews. The key findings suggested significant improvements in users' well-being, showing the potential of AI-enhanced mobile applications as an effective tool for improving well-being and mental health.
Vedoucí práce: Marcel Valový
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses